Planning Machinery in India - Planning Commission (Planning Commission)
The idea of a co-ordinated or planned effort for promoting rapid development of the economy was an integral part of the nationalist thinking in India long before Independence. Ever since 1876 when Dadabhai Naoroji published his paper on Poverty of India, Indian leaders had criticised the economic policy followed by the then ruling power in India as one of the main causes of the economic decadence of the country and urged that it was only co-ordinated action for economic development taken by a popular Government in the interest of the people of the country that could develop the economy and lead the people out of grinding poverty. As the struggle for national independence progressed, its social and economic aims became more definite.
Joint Secretary, Planning Commission